2019
DOI: 10.11591/ijpeds.v10.i3.pp1157-1166
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two potential recuperating converters in DC railway electrification system for harmonic mitigation

Abstract: <span>The regenerative braking energy produced by Light-Rail-Transit (LRT) train is commonly transferred back to power grid via a conventional three-phase inverter (recuperating converter). Although this is a cost saving solution but the ac grid current and voltage waveforms were distorted. Hence passive filters are integrated to mitigate the harmonics. This paper proposed to replace the conventional inverter system with a multilevel converter. Cascaded H-Bridge (CHB) converter and Modular Multilevel Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In urban and suburban areas that typically adopt direct current (DC) third rail systems [1]- [3], the rolling stocks are powered by a 33 kV medium-voltage (MV) distribution network through rectifiers [4]- [6]. The abundant usage of rectifiers in the third rail systems can cause severe harmonic distortion [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…In urban and suburban areas that typically adopt direct current (DC) third rail systems [1]- [3], the rolling stocks are powered by a 33 kV medium-voltage (MV) distribution network through rectifiers [4]- [6]. The abundant usage of rectifiers in the third rail systems can cause severe harmonic distortion [7]- [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, as the traction rectifier is uncontrolled, power resistors must be activated to comsume braking energies harvested by a stopping train Figure 1(a). Literatures [5], [6], had proposed to introduce a DC power recuperating system to transmit the braking energy back to the utility grid. Some simulation studies have concluded that about 10% to 40% of energy saving could be achieved with a recuperating system [7], [8].…”
Section: Introductionmentioning
confidence: 99%